Investor Behaviour in Derivatives Market (International Journal of Psychosocial Rehabilitation, 2020)
Derivatives market has seen a tremendous growth in India during the last two decades. It has become relevant to understand investors perception and behavior as well as the factors that influence it for appreciating long term sentiments of this market. The objective of this paper was to analyze the investor behavior in Indian derivatives market. In the light of investment features like frequency of investment in derivatives, investors experience in derivatives trading, method of trading, profit earned, objective of investment, percentage of investment, perceived risk of derivatives market, and importance of derivatives market in India. These investor behavior characteristics have also been analyzed on the basis of demographics wise differences in Indian investors. For the purpose of the study, a structured questionnaire was administered, and responses were received from 432 respondents. The results reveal that investor behavior in derivatives market which is governed by various factors mentioned above are affected by demographic variable of the investor like gender, age, nature of employment, workplace activity, work experience, annual family income, educational background.